2010
DOI: 10.1111/j.1365-2141.2010.08139.x
|View full text |Cite
|
Sign up to set email alerts
|

A United Kingdom Haemophilia Centre Doctors’ Organization guideline approved by the British Committee for Standards in Haematology: guideline on the use of prophylactic factor VIII concentrate in children and adults with severe haemophilia A

Abstract: Newcastle Hospitals NHS Trust, UK SummaryConsensus-based guidelines supported by the literature are presented on the role of prophylactic administration of factor VIII concentrate in children and adults with severe haemophilia A. The timing of initiation of prophylaxis, the choice of prophylactic regimen, monitoring, management of breakthrough bleeding and education of the patient and family are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
125
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(130 citation statements)
references
References 67 publications
1
125
0
4
Order By: Relevance
“…6,7 For older patients, guidelines on dosing are unavailable, 44,45 and the recommendation is to just keep this dose, 45 despite the fact that adults have more regulated activity patterns, a longer FVIII half-life, and a weaker association between trough levels and bleeding. 46,47 For clinical practice, it will always be important to prevent bleeding, especially in joints.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 For older patients, guidelines on dosing are unavailable, 44,45 and the recommendation is to just keep this dose, 45 despite the fact that adults have more regulated activity patterns, a longer FVIII half-life, and a weaker association between trough levels and bleeding. 46,47 For clinical practice, it will always be important to prevent bleeding, especially in joints.…”
Section: Discussionmentioning
confidence: 99%
“…National guidelines and recommendations issued in several European countries advised starting prophylaxis early, 8,13 often combining criteria of both age and number of bleeds at initiation of prophylaxis. The results of this study confirm that there is an increasing tendency not only to start prophylaxis before the age of three years or before the second joint bleed, but also that more patients start on primary prophylaxis.…”
Section: -10mentioning
confidence: 99%
“…Only one publication was identified that fulfilled the criterion for group I [25]. This recent publication summarizes a guideline on the use of prophylactic FVIII concentrate in children and adults with severe haemophilia A from the United Kingdom Haemophilia Centre Doctors' Organization (UKHCDO).…”
Section: Prophylaxis Guidelines In Adult Haemophilia Patientsmentioning
confidence: 96%